PERUBAHAN BUNYI PADA TUTURAN RESMI YANG DIGUNAKAN MAHASISWA IAIN SYEKH NURJATI CIREBON - Ayu Fauziyah; Indrya Mulyaningsih (Jurusan Tadris Bahasa Indonesia, 2016)
One of the factors causing a change in the sound of Indonesian environmental factors. For example the word /Sabtu/ in Indonesian commonly pronounced /Saptu/. It is seen a [b] turned into a [p] as a result of the influence of the sound [t]. This paper aims to explain the change of sound in speech used students in IAIN Syekh Nurjati Cirebon. The results showed that students in IAIN Syekh Nurjati Cirebon less careful in using pronouncing. Students still mixing the languages to official situations with language in informal situations.